2000
DOI: 10.1093/emboj/19.15.4015
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of PI 3-kinase by Ruk, a novel adaptor protein

Abstract: Class I A phosphatidylinositol 3-kinase (PI 3-kinase) is a key component of important intracellular signalling cascades. We have identi®ed an adaptor protein, Ruk l , which forms complexes with the PI 3-kinase holoenzyme in vitro and in vivo. This interaction involves the proline-rich region of Ruk and the SH3 domain of the p85a regulatory subunit of the class I A PI 3-kinase. In contrast to many other adaptor proteins that activate PI 3-kinase, interaction with Ruk l substantially inhibits the lipid kinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
145
0
7

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 78 publications
5
145
0
7
Order By: Relevance
“…It should be noted that while numerous adapter-like proteins are known to associate with the PI3K holoenzyme to activate its function, to our knowledge only two proteins have been identified that suppress PI3K activity: our protein PIK3IP1 and the negative regulator Ruk [17]. Unlike Ruk which binds to the SH3 domain of p85 alpha to reduce PI3K activity [17], PIK3IP1 is unique in that it binds directly to p110 to down modulate PI3K.…”
Section: Pik3ip1 Overexpression Augments Staurosporine Induced Apoptosismentioning
confidence: 99%
“…It should be noted that while numerous adapter-like proteins are known to associate with the PI3K holoenzyme to activate its function, to our knowledge only two proteins have been identified that suppress PI3K activity: our protein PIK3IP1 and the negative regulator Ruk [17]. Unlike Ruk which binds to the SH3 domain of p85 alpha to reduce PI3K activity [17], PIK3IP1 is unique in that it binds directly to p110 to down modulate PI3K.…”
Section: Pik3ip1 Overexpression Augments Staurosporine Induced Apoptosismentioning
confidence: 99%
“…We have recently identified a novel adaptor-type protein named Ruk [11]. It has been cloned by other groups and named Cin85 or SETA [12,13].…”
mentioning
confidence: 99%
“…Although the precise role of this Ruk/CD2AP family is still unknown, they are involved in the control of apoptosis and the regulation of cytoskeletal architecture [11,13,[15][16][17][18].…”
mentioning
confidence: 99%
“…Ruk/CIN85 plays a role in various biological processes including control of receptor tyrosine kinase signalling [1,9,18,27,28,32], rearrangement of actin cytoskeleton [30], neuronal and T cell apoptosis [5,15,26], herpes simplex virus 1 infection [21], adhesion [30] and invasion [25]. Overexpression of Ruk l /CIN85 full-length form induces apoptotic cell death of primary neurons in culture [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Ruk l /CIN85 full-length form induces apoptotic cell death of primary neurons in culture [2,15]. However, shorter molecular forms of Ruk/CIN85 block the pro-apoptotic effect of Ruk l /CIN85, suggesting that expression of different combinations of Ruk/CIN85 proteins in cells could be involved in the regulation of their survival and other intracellular processes [2,15]. CD2AP/CMS is required for rapid activation of PI3K and ERK/MAPK pathways by TGF-β [29].…”
Section: Introductionmentioning
confidence: 99%